Out of style: reanimating stylistic study in composition and rhetoric - Butler, Paul, author; Utah State University Press, publisher (Colorado State University. Libraries, 2008)
Study of stylistics in written English and rhetoric.
Introduction: Reanimating style in composition and rhetoric -- Historical developments: relevant stylistic history and theory -- Our of style: reclaiming an "inventional" style in composition -- Style in the diaspora of composition studies -- Style and the public intellectual: rethinking composition in the public sphere -- Back in style: style and the future of composition studies.
Keywords: Language and languages -- Style; Rhetoric